STRATEGI KEUANGAN DALAM MENINGKATKAN KUALITAS MANAJEMEN KEUANGAN DI SMPN 3 CILEGON - Halabi, Ahmad; Rahmulyana, Anjar; Hayadi, B. Herawan; Yusuf, Furtasan Ali (Yayasan Education and Social Center, 2024)
This research aims to analyze and evaluate the financial strategies implemented in improving the quality of financial management at SMPN 3 Cilegon. Good quality financial management in schools is a crucial factor in supporting the achievement of educational goals and human resource development. The research method used is a qualitative approach. Data was collected through observation, interviews and analysis of documents related to school finances. This research will focus on identifying financial strategies that have been implemented, such as budget allocation, financial resource management, and financial performance evaluation. SWOT analysis will be used to evaluate strengths, weaknesses, opportunities and threats in implementing financial strategies at SMPN 3 Cilegon. It is hoped that the research results will provide a deeper understanding of the effectiveness of the financial strategies that have been implemented, as well as provide recommendations for improvements to improve financial management at SMPN 3 Cilegon. The implications of this research can be a basis for policy makers, school principals and related parties in designing strategic policies that are more effective in improving the quality of financial management in secondary level educational institutions